2000
DOI: 10.1002/1099-0755(200005/06)10:3<179::aid-aqc403>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Assessing stream quality using information on mesohabitat distribution and character

Abstract: 1. The purpose of this paper is to demonstrate: (i) how mesohabitats—medium‐scale habitats which arise through the interactions of hydrological and geomorphological forces—can be used as a basis for assessing instream habitat diversity; (ii) how combining data on mesohabitat distribution with those from macroinvertebrate sampling can produce an index for assessing stream quality; and (iii) how, when nested with River Habitat Survey (RHS), mesohabitat information can provide a comprehensive assessment of stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 12 publications
1
44
0
5
Order By: Relevance
“…Hydromorphological conditions play an important role in these monitoring programs (REFCOND, 2003;CEN, 2004). Consequently, many countries now have sampling protocols and indices that require information on mesohabitat recognition and characterisation to evaluate hydromorphological conditions (e.g., Raven et al, 1997;LAWA, 2000;Tickner et al, 2000;Pardo et al, 2002;Fernández et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hydromorphological conditions play an important role in these monitoring programs (REFCOND, 2003;CEN, 2004). Consequently, many countries now have sampling protocols and indices that require information on mesohabitat recognition and characterisation to evaluate hydromorphological conditions (e.g., Raven et al, 1997;LAWA, 2000;Tickner et al, 2000;Pardo et al, 2002;Fernández et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…An HMU exhibits distinctive hydraulic properties and a characteristic channel cross-section (Dollof et al, 1993;Parasiewicz et al, 2009). This concept is similar to the mesohabitat concept previously used in other studies (Vadas & Orth, 1998;Tickner et al, 2000;Schwartz & Herricks, 2008). In this paper, we treat mesohabitat and hydromorphological unit as synonyms.…”
Section: Data Collectionmentioning
confidence: 99%
“…Para completar la caracterización del ensamble bentónico de cada sitio se determinó el Índice de Preferencia Relativa (IPR) (tiCkner et al, 2000), dividiendo la abundancia de cada taxa en una cierta situación de muestreo (sitios, hábitats y fechas) por su abundancia total registrada en todas las muestras colectadas. Además, para investigar qué taxa son indicadores ecológicos de un sitio particular, se utilizó el Método de Valor Indicador (Indicator Value -IndVal) propuesto por dufrene & legendre (1997), que integra en un valor porcentual, la frecuencia de ocurrencia (fidelidad) y la abundancia relativa (concentración) de las especies de un hábitat determinado.…”
Section: Materials Y Métodosunclassified
“…En el área de piedemonte se encuentra emplazada la Presa Achiras, cuya construcción culminó a comienzos de 2008. Esta presa, con una altura de 23 m, controlará las amenazas de eventos catastróficos las comunidades acuáticas originales, sus variaciones espacio-temporales, los listados taxonómicos de especies, su biología, sus requerimientos de hábitat y su rango geográfico pasado y presente son conocimientos que constituyen la base para la protección legal de especies amenazadas por acciones antrópicas, y la conservación y recuperación de hábitats (tiCkner et al, 2000;ArmitAge, 2006;strAyer, 2006).…”
unclassified
“…Field data is collected using a standard continuous observation along 500 m length of river channel (called sweep up) and by 10 transects (spot checks) separated by 50 m. In this study, we carried out RHSm over a total segment length of only 50 m comprising five spot checks 10 m apart and sweep up along the total length of the reduced segment. The objective was to achieve a better relationship between the biological data and habitat descriptors since several authors have found a weak association between RHS and biological data mainly attributable to the different spatial scales of each type of analysis, i.e., biological data such as benthic fauna are obtained from sets of micro-habitats while RHS data derives from a larger scale of one or more meso-habitats (Cortes et al 2008;Davenport et al 2004;Tickner et al 2000).…”
Section: River Corridor and Fluvial Habitatmentioning
confidence: 99%